2021
DOI: 10.1111/ivb.12321
|View full text |Cite
|
Sign up to set email alerts
|

Mobile learning applications to improve invertebrate zoology online teaching

Abstract: The use of new technologies including personal mobile devices has become an indispensable tool in our daily lives, and thus its presence in education is becoming ever more ubiquitous. In the current scenario imposed by the COVID‐19 pandemic, in which in‐person presence in classrooms has been enormously reduced at all educational levels, the use of mobile learning and cutting‐edge methods can greatly improve the way students learn and enhance their online‐learning experience. Mobile applications, combined with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 27 publications
0
21
0
Order By: Relevance
“…English mobile learning refers to that learners obtain learning resources and communicate with others at any place and at any time they need to learn through wireless communication networks and mobile devices such as PDA and mobile phone. Mobile learning is the product of the integration of digital learning and mobile computer technology [1,2]. English mobile learning has brought a new learning mode for English learners and a new feeling that they can learn at any time and anywhere.…”
Section: Introductionmentioning
confidence: 99%
“…English mobile learning refers to that learners obtain learning resources and communicate with others at any place and at any time they need to learn through wireless communication networks and mobile devices such as PDA and mobile phone. Mobile learning is the product of the integration of digital learning and mobile computer technology [1,2]. English mobile learning has brought a new learning mode for English learners and a new feeling that they can learn at any time and anywhere.…”
Section: Introductionmentioning
confidence: 99%
“…Others, such as Eugene et al (2021), Middlebrooks and Salewski (2021), and Schulze et al (2021) work well for situations in which students cannot access campus but retain some access to the field sites being studied. Verdes et al (2021), The Virtual Field Project (https://thevirtualfield.org/), and this article present ways that students without access to campus, to specialized equipment, or to the field sites can nonetheless experience important aspects of research and field studies. Specifically, the methods presented here were successful in providing remote, online students with field experiences, with detailed study of a wide variety of local macroinvertebrates, and with participation as a collaborative team in a genuine research project.…”
Section: Resultsmentioning
confidence: 94%
“…In the feedback to the students 7% indicated that the questions were asked during classes. Nonetheless, studies were also identified in which learning evaluations were not carried out [13] Figure 4 shows the number of learning assessment tools that were used to evaluate those who utilized VR, with questionnaires being the most widely used; having exponential growth in recent years. In Table VI it can be observed that the studies were generally done through the use of Google Cardboard (19%), Desktop VR technology (25%), Oculus Rift technology (19%), HTC VIVE technology (9%), Samsung GearVR technology (6%), and other Mobile Client technologies (16%).…”
Section: Resultsmentioning
confidence: 99%
“…In the feedback to the students 7% indicated that the questions were asked during classes. Nonetheless, studies were also identified in which learning evaluations were not carried out[13] [14] [22] [17] [21] [25].Figure4shows the number of learning assessment tools that were used to evaluate those who utilized VR, with questionnaires being the most widely used; having exponential growth in recent years.…”
mentioning
confidence: 99%